The Role of Hydrochar as Anaerobic Digestion Process Additive and CO2 Adsorbent - Annalinda Capone; Antonio Panico; Annarita Travaglino; Lucio Zaccariello; Hèlène Ageorges; Biagio Morrone (Chemical Engineering Transactions)
Hydrothermal Carbonization (HTC) is a thermochemical process that converts wet biomass into three main products: gas, liquid, and solid phase. The solid phase, hydrochar, can act as an accelerator of methane production. This article focuses on the sequential integration of HTC with Anaerobic Digestion (AD) utilizing HTC products as a boost to the AD process and CO2 capture. This study investigates the sequential integration of HTC and AD, evaluating the effect of hydrochar addition on methane production from sewage sludge under mesophilic (35°C) conditions. Various hydrochar dosages (0.5 g, 2 g, 5 g, and 8 g) were tested in batch reactors. The main outcomes indicate that hydrochar addition increased cumulative methane production in AD by up to 1100 mL under mesophilic conditions (35°C) with a 5 g hydrochar dosage, representing the optimal enhancement.In addition, the study assesses the influence of different operational parameters, such as temperature, pressure, and hydrochar feedstock, on CO2 adsorption efficiency. By examining these variables, the study also aims to identify optimal conditions for maximizing CO2 capture, considering that chemical activation can enhance the adsorption properties of hydrochar. Comparing the effects of hydrochar in improving the performance of both AD and CO2 capture processes with those of existing materials provides a benchmark for evaluating the practical applicability of hydrochar in industrial activities.